PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN SAHAM, DAN VOLATILITAS RETURN SAHAM PADA BID-ASK SPREAD - Wahyuliantini, Ni Made; Suarjaya, Anak Agung Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 9 Nomor 2 Tahun 2015)
The purpose of this study is to analize the effect of stock price, stock trading volume, and volatility of stock returns on bid-ask spread. The population of this study is 20 companies incorporated in LQ45 index that appear successively during the observation period of 2011-2013. Sampling method used was saturated sampling technique, so all companies used as sample. Hipotheses were examined by implementing multiple linear regression analysis. The results show that stock price negatively affect bid-ask spread, while stock trading volume and volatility of stock returns has no significant effect on bid-ask spread.
Keywords: stock price, trading volume, volatility of stock returns, bid-ask spread